Implementasi Sistem Informasi Muselok Menggunakan Augmented Reality Berbasis Android - Saputra, Doni; Krisna Juliharta, I Gede Putu; Wahyu Nirmala, Bagus Putu (JURNAL DESTINASI PARIWISATA; Vol 8 No 1 (2020): VOL 8, NO 1 (2020): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2020.v08.i01.p21, 2020)
Multimedia development methods with several stages such as, concept, design, material collecting, assembly, testing and distribution, with these stages can produce multimedia products. Therefore, researchers developed a Muselok application based on the method of Luther-Sutopo combine with qualitative approach. This application build to show the collection of NTB Museum. Negeri Nusa Tenggara Barat / NTB as a technology Augmented Reality / AR. From the results of making the Muselok application by using the method of Luther-Sutopo, it was found that, during the implementation, several flow changes were made during the Muselok application making process, assembly process and testing process can be changed repeatedly until it was difficult to find the problem points of the application. From the Muselok application users there is constructive and positive feedback even though there are still some shortcomings in terms of the Muselok application interface.However, it must be realized that technical aspects was not the main problem. In fact, the process between the museum manager, the design team and the views of experts were dificult to combining their’s perspective. In the future, a transdisciplinary approach is needed to be able to produce the right technology, according to needs and provide added value even in technology research especially in the related with tourism as a science. Keywords: Augment Reality, Muselok Application, Luther -Sutopo, Museum, Tourism